(untitled) (Asian Journal of Pharmaceutical and Health Sciences, 2018)
The objective of the present investigation was to conduct phytochemical screening of phenolic content and antioxidant activity of various leaf and bark extracts of Macaranga peltata. Antioxidants are the substances which inhibit oxidation, which have the ability to remove the potentially damaging oxidizing agents in a living organism. Many phytochemicals present in the plants are able to reduce or prevent the oxidative damage to the human cells which can cause even cancer in humans. DPPH (1, ldiphenyl-2-picryl hydrazyl) radical was used for evaluation of free radical scavenging and the total phenolic content was determined by folin-Ciocalteau reagent. The IC50 values were calculated and the antioxidant activity of various extract were compared with ascorbic acid. The ethanol extracts ofboth leaves and barks produced a comparatively higher antioxidant activity than methanol and hexane extracts. The result indicates the antioxidant activity of the extracts and the correlation between the total phenolic content and antioxidant activity.